Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve the given system of linear equations:
[tex]\[ \begin{cases} 3x - 4y = -6 \\ 2x + 4y = 16 \end{cases} \][/tex]
we will use the method of elimination.
1. Add the equations to eliminate [tex]\(y\)[/tex]:
Let's add the two equations together. This will allow us to eliminate the [tex]\(y\)[/tex] term since the coefficients of [tex]\(y\)[/tex] are opposites ([tex]\(-4y\)[/tex] and [tex]\(+4y\)[/tex]).
[tex]\[ (3x - 4y) + (2x + 4y) = -6 + 16 \][/tex]
Simplify:
[tex]\[ 3x + 2x - 4y + 4y = -6 + 16 \][/tex]
[tex]\[ 5x = 10 \][/tex]
2. Solve for [tex]\(x\)[/tex]:
[tex]\[ 5x = 10 \][/tex]
Divide both sides by 5:
[tex]\[ x = 2 \][/tex]
3. Substitute [tex]\(x = 2\)[/tex] back into one of the original equations to solve for [tex]\(y\)[/tex]:
We can use either of the original equations. Let's use the first one:
[tex]\[ 3x - 4y = -6 \][/tex]
Substitute [tex]\(x = 2\)[/tex]:
[tex]\[ 3(2) - 4y = -6 \][/tex]
Simplify:
[tex]\[ 6 - 4y = -6 \][/tex]
Subtract 6 from both sides:
[tex]\[ -4y = -6 - 6 \][/tex]
[tex]\[ -4y = -12 \][/tex]
Divide both sides by -4:
[tex]\[ y = 3 \][/tex]
4. Conclusion:
The solution to the system of equations is:
[tex]\[ x = 2, \quad y = 3 \][/tex]
So, the point of intersection of the two lines described by the system of equations is [tex]\((2, 3)\)[/tex].
[tex]\[ \begin{cases} 3x - 4y = -6 \\ 2x + 4y = 16 \end{cases} \][/tex]
we will use the method of elimination.
1. Add the equations to eliminate [tex]\(y\)[/tex]:
Let's add the two equations together. This will allow us to eliminate the [tex]\(y\)[/tex] term since the coefficients of [tex]\(y\)[/tex] are opposites ([tex]\(-4y\)[/tex] and [tex]\(+4y\)[/tex]).
[tex]\[ (3x - 4y) + (2x + 4y) = -6 + 16 \][/tex]
Simplify:
[tex]\[ 3x + 2x - 4y + 4y = -6 + 16 \][/tex]
[tex]\[ 5x = 10 \][/tex]
2. Solve for [tex]\(x\)[/tex]:
[tex]\[ 5x = 10 \][/tex]
Divide both sides by 5:
[tex]\[ x = 2 \][/tex]
3. Substitute [tex]\(x = 2\)[/tex] back into one of the original equations to solve for [tex]\(y\)[/tex]:
We can use either of the original equations. Let's use the first one:
[tex]\[ 3x - 4y = -6 \][/tex]
Substitute [tex]\(x = 2\)[/tex]:
[tex]\[ 3(2) - 4y = -6 \][/tex]
Simplify:
[tex]\[ 6 - 4y = -6 \][/tex]
Subtract 6 from both sides:
[tex]\[ -4y = -6 - 6 \][/tex]
[tex]\[ -4y = -12 \][/tex]
Divide both sides by -4:
[tex]\[ y = 3 \][/tex]
4. Conclusion:
The solution to the system of equations is:
[tex]\[ x = 2, \quad y = 3 \][/tex]
So, the point of intersection of the two lines described by the system of equations is [tex]\((2, 3)\)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.